ANALYSIS OF AVAILABLE METHODS FOR ASSESSING THE LEVEL OF ECONOMIC SECURITY OF AN ENTERPRISE FOR CONDUCTING MODERN DIAGNOSTICS OF ITS FINANCIAL CONDITION (INNOVATIVE ECONOMY, 2020)
Melikhova T.O. ANALYSIS OF AVAILABLE METHODS FOR ASSESSING THE LEVEL OF ECONOMIC SECURITY OF AN ENTERPRISE FOR CONDUCTING MODERN DIAGNOSTICS OF ITS FINANCIAL CONDITIONPurpose. The purpose of the work is to analyze existing methods of assessing the level of economic security of an enterprise for conducting a modern diagnosis of its financial status in order to select the most appropriate methodology at the enterprise level. Methodology of research.The theoretical and methodological basis of the research is the situation of modern economic theory, scientific works of scientists, normative and legislative acts of Ukraine on the issues of assessing the level of economic security. In the process of research, the following methods were used: abstract-logical (to identify the essence of assessing the level of economic security as an economic category), analysis and synthesis, logical generalization, monographic (in the study of methods for assessing the level of economic security of enterprises). Findings.  The analysis of the methods of assessing the level of economic security of the enterprise, given in the scientific literature, showed that among scientists there are different approaches, both to the choice of the methods themselves and the system of indicators or criteria of calculation. The critical analysis and generalized methods of assessing the economic security of enterprises are carried out, namely: 1. Methodology based on the functional components of economic security. 2. Methodology based on the indicator approach to assess the economic security of the enterprise. 3. Methodology based on an investment approach to assess the economic security of an enterprise. 4. Method of assessing the economic security of the enterprise is based on the approach of availability of net profit. 5. Methodology for assessing the level of economic security of an enterprise, which is based on a resource-functional approach, the calculations of which are carried out using an integral indicator. 6. Methodology for assessing the level of economic security of an enterprise, which is built on the basis of ball scores, when the basis for determining the level of safety are the limit values of the indicators and their rating. 7. Methodology for assessing the level of economic security of an enterprise that calculates an integral indicator of economic security in accordance with market value and economic security of its capital. Scientists give different methods and distinguish them different indicators. The most commonly used integral indicator, but the essence of any methodology for assessing the level of economic security of the enterprise remains in the study of the impact of the components on its overall level of economic security. Also, in each branch of the enterprises there are their peculiarities, since the importance of the influence of the selected components on the overall level of economic security depends on the type of its activity. Originality.It is necessary to summarize the existing methods of assessing the level of economic security of the enterprise to conduct a modern diagnosis of its financial condition.Practical value.The obtained results of the research are the basis for development of the author’s methodology for calculating the period of returning investments in order to assess the incurred costs for the establishment of the company’s economic security service in the short-and long-term. Key words: analysis; methodology; assessment; level; economic safety of the enterprise; financial condition. Melikhova T.O. ANALYSIS OF AVAILABLE METHODS FOR ASSESSING THE LEVEL OF ECONOMIC SECURITY OF AN ENTERPRISE FOR CONDUCTING MODERN DIAGNOSTICS OF ITS FINANCIAL CONDITIONPurpose. The purpose of the work is to analyze existing methods of assessing the level of economic security of an enterprise for conducting a modern diagnosis of its financial status in order to select the most appropriate methodology at the enterprise level. Methodology of research.The theoretical and methodological basis of the research is the situation of modern economic theory, scientific works of scientists, normative and legislative acts of Ukraine on the issues of assessing the level of economic security. In the process of research, the following methods were used: abstract-logical (to identify the essence of assessing the level of economic security as an economic category), analysis and synthesis, logical generalization, monographic (in the study of methods for assessing the level of economic security of enterprises). Findings.  The analysis of the methods of assessing the level of economic security of the enterprise, given in the scientific literature, showed that among scientists there are different approaches, both to the choice of the methods themselves and the system of indicators or criteria of calculation. The critical analysis and generalized methods of assessing the economic security of enterprises are carried out, namely: 1. Methodology based on the functional components of economic security. 2. Methodology based on the indicator approach to assess the economic security of the enterprise. 3. Methodology based on an investment approach to assess the economic security of an enterprise. 4. Method of assessing the economic security of the enterprise is based on the approach of availability of net profit. 5. Methodology for assessing the level of economic security of an enterprise, which is based on a resource-functional approach, the calculations of which are carried out using an integral indicator. 6. Methodology for assessing the level of economic security of an enterprise, which is built on the basis of ball scores, when the basis for determining the level of safety are the limit values of the indicators and their rating. 7. Methodology for assessing the level of economic security of an enterprise that calculates an integral indicator of economic security in accordance with market value and economic security of its capital. Scientists give different methods and distinguish them different indicators. The most commonly used integral indicator, but the essence of any methodology for assessing the level of economic security of the enterprise remains in the study of the impact of the components on its overall level of economic security. Also, in each branch of the enterprises there are their peculiarities, since the importance of the influence of the selected components on the overall level of economic security depends on the type of its activity. Originality.It is necessary to summarize the existing methods of assessing the level of economic security of the enterprise to conduct a modern diagnosis of its financial condition.Practical value.The obtained results of the research are the basis for development of the author’s methodology for calculating the period of returning investments in order to assess the incurred costs for the establishment of the company’s economic security service in the short-and long-term. Key words: analysis; methodology; assessment; level; economic safety of the enterprise; financial condition.  financial security of the enterprise”, available at: file:///C:/Users/Nout/Downloads/assessment-of-level-of-financial-security-company.pdf (access date December20, 2017). 3.      Khalina, V.Yu. (2014), “Methodical approach to assessing the level of economic security of the enterprise”, available at: http://nbuv.gov.ua/UJRN/Vchtei_2014_1_24 (access date December20, 2017). 4.      Nahorna, I.I. “Estimation of Sustainable Economic Security of an Industrial Enterprise”, available at: 241_nagorna_i.i._ocinka_stijkoi_ekonomichnoi_bezpeki_promislovogo pidpriemstva (access date December20, 2017). 5.      Illiashenko, O.V. (2016), “Methodological basis of forming and functioning of mechanisms of enterprise economic security system”, Dissertation for Dr. Sc. (Econ.), Kyiv, Ukraine, 606 p. 6.      Hryshko, N.Ye. (2013), “Formation of the estimated parameters of the economic safety components of the machine-building enterprise”, Visnyk sotsialno-ekonomichnykh doslidzhen, iss. 1, pp. 62-69. 7.      Yaremenko, O.F. (2009), “Mechanism of management of economic safety of machine-building enterprise”,Thesis abstract for Cand. Sc. (Econ.), Khmelnitsky, Ukraine, 20 p. 8.      Shlemko, V.T. and Binko I.F. (1997),Ekonomichna bezpeka Ukrayiny: sutnist i napryamky zabezpechennya [Economic security of Ukraine: the essence and directions of the provision], monograph, NISD, Kyiv, Ukraine,144 p.  9.      Kozachenko, G.V., Ponomarev, V.P. and Lyashenko, O.M. (2003), Ekonomicheskaya bezopasnost: sushchnost i mekhanizmy obespecheniya [Economic security: the essence and mechanisms of provision],monograph, Libra, Kyiv, Ukraine, 280 p. 10.    Pilova, D.P. (2007), “Formation and estimation of economic safety of mining and concentrating enterprises”,Thesis abstract for Cand. Sc. (Econ.), Kryvyi Rih, Ukraine, 16 p. 11.    Pokropyvnyi, S.F (2000), Ekonomika pidpryiemstva[Economy of the enterprise
Keywords: Key words; analysis; methodology; assessment; level; economic safety of the enterprise; financial condition.